Population diversity of Theileria annulata in Portugal - Gomes, J.; Salgueiro, P.; Inácio J; Amaro A; PintoJ; Tait A.; Shiels B.; Pereira da Fonseca I; Santos-Gomes G; Weir W. (Infection, Genetics and Evolution, 2016)
The tick-borne protozoan parasite Theileria annulata causes tropical theileriosis, a severe disease of cattle that occurs across the Mediterranean littoral, the Middle East and Southern Asia. In the Mediterranean region, the disease has long been perceived as being a constraint to livestock production in North Africa and Turkey but was believed to have minimal impact in Southern European countries. It has recently been demonstrated that in Southern Portugal the prevalence of T. annulata is approximately 30%. While the population genetics of the parasite and the multiplicity of infection in the bovine host have been studied in a number of countries, no information is currently available on the composition of the parasite population in Southern Europe or its relationship to populations in bordering regions. A parasite genotyping system, based on micro- and mini-satellite amplification, was used to perform genetic analysis of T. annulata populations from T. annulata infected cattle in twelve farms in Southern Portugal. A diversity of genotypes and a high multiplicity of infection were found, suggesting that the parasite possesses a panmictic population in this region. In comparison with genotypes found in Tunisia and Turkey, parasites from Portugal form a genetically distinct group and show lower genetic diversity.